Digital Leadership in the Public Sector-Systematic Literature Review : Systematic literature review - Riki Nuryadin; A Sobandi; Budi Santoso (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
This paper examines digital leadership in the public sector which is one of the challenges faced by many government organizations in adopting and managing information and communication technology effectively, the use of ICT changes the way of working and business operations of an organization both in the public and private sectors. Digital transformation opens up opportunities and challenges to create business advantage by using the concept of digital capability as the ability of an organization o understand digital technology and use it to create business value, digital transformation is not only about implementing new technology, but also about changing the way of thinking and managing the business as a whole. Digitalisation and e-leadership can help improve transparency, accountability and public participation in decision-making processes in local government. In addition, local leaders are also using digital technology to improve communication with the public and get useful feedback in public policy making. In conclusion, digital leadership in the public sector is essential for governments and public sector organizations to keep pace with the rapid changes brought about by digital transformation. Effective digital leadership can help improve the efficiency, quality, transparency, participation and accessibility of public services, ultimately delivering better outcomes for citizens.